Incidencia de la neuromotricidad en el desarrollo de los patrones motrices básicos de los niños escolarizados con Síndrome de Down de la Escuela Especial 3 de Diciembre, del cantón Vinces - Naranjo Vera, Jonathan Jacinto (2021)
The purpose of this research was to evaluate the basic motor patterns in school children with Down Syndrome, from the Special School "3 de Diciembre", Canton Vinces, from a neuromotor approach. Methodology: an intentional sample of ten children (7 males and 3 females) was selected through a non-probability sampling; with a non-experimental cross-sectional research design. The “EVANM” neuromotor evaluation test proposed by the authors Díaz-Jara et al. (2015) to know the state of the eight basic motor patterns (crawling, crawling, walking, setting, running, muscle tone, balance, postural control) - (not acquired, in process or acquired / automated). Results: all school children with Down Syndrome from the “3 de Diciembre” Special School who were evaluated, did not have acquired the basic motor patterns of set and balance, presenting a high index of clumsy and uncoordinated movements in each action performed; while 57% still do not acquire the patterns of entrainment and muscle tone; Nevertheless; crawling (57%), gait (57%), running (57%) and postural control (71%) are in the process of development; Likewise, it is evident that the sample presents problems of writing, reading, communication, proprioception, among others. Finally, according to the unanimous evaluation, it was evidenced that boys have better motor development than girls in the patterns of dragging, running, gait and muscle tone.